The Wal-Mart supply chain controversy - Smith, N. Craig, 1958-; Crawford, Robert J. (London : NeilsonJournals Publishing, 2006)
Wal-Mart received widespread praise for its response to Hurricane Katrina when it hit the Louisiana coast in August 2005 and low prices at the world's largest retailer are estimated to save consumers billions of dollars a year. Nonetheless, it was coming under increasing criticism for core business practices, ranging from detrimental effects on communities when Wal-Mart stores are established, to abusive labour practices, to alleged sourcing from sweatshops. This case looks at the benefits and the potentially harmful consequences of the Wal-Mart business model. The focus is on supply chain issues and, more specifically, a lawsuit brought by the International Labor Rights Fund (ILRF) charging that Wal-Mart failed to meet contractual obligations specified in its Standards for Suppliers Agreement. However, the retailer must respond to a range of criticisms that chief executive Lee Scott recognizes are harming its reputation. Scott asks, in reference to Wal-Mart's response to Katrina, "what would it take for Wal-Mart to be that company, at our best, all the time?" More fundamentally, the case asks, how sustainable is Wal-Mart's business model?
Originally Published InSmith, N. C., & Crawford, R. J. (2006). The Wal-Mart supply chain controversy. Journal of Business Ethics Education, 3(1), 143-164. JBEE3-0CS2.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Scott, Lee; Wal-Mart (Firm) -- Case studies; Discount houses (Retail trade) -- United States -- Case studies; Big business -- Social aspects -- United States -- Case studies; Marketing -- Management -- Case studies